Serum Magnesium Concentration in Patients with Leukemia and Lymphoma - Merza, Wafa M.; majid, Ali Y.; Daoud, Munaf S.; Jawad, Ali M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Leukemias and lymphomas are malignant disorders that occur in the blood forming organs and lymphoid tissue respectively. They are classified to types and several subtypes such as acute or chronic, lymphocytic or myelocytic and T-cell or B-cell lymphocytic for leukemias and histologically into Hodgkin’s and Non-Hodgkin’s for lymphomas. Literatures do not contain many research work on magnesium in patients with these disorders, although this mineral is essential for many metabolic, enzymic, regulatory and immune reactions in the human body. Therefore, the present study was aimed to evaluate the level of magnesium in the sera of patients with different types of leukemia and lymphoma.Patients and Methods: Fifty five patients with leukemia and lymphoma and twenty five healthy controls were studied. The patients were attendants of Baghdad Teaching Hospital and Pediatric Teaching Hospital from September 2006 to January 2007. The diagnosis was confirmed by examination of both peripheral blood, lymph node biopsy and/or bone marrow examination. Patients were categorized according to French-American-British Criteria. Thirty five patients with ALL, one with CLL, six with AML, three with CML, three with HL and seven with NHL. Venous blood was collected from each patient or control person and sera were obtained by centrifugation. S[Mg] was measured by Atomic Absorption Flame Spectrophotometry.Results:The Mean ± SD of S[Mg] in mg/dl of all types of leukemic and lymphomatous patients was lower than the controls. There was a high statistically significant difference (P